LA JOYA EARTHEN PYRAMID AFTER HURRICANE KARL, SEPTEMBER 2010, ON THE GULF COAST OF MEXICO - Daneels, Annick; Guerrero Baca, Luis Fernando (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
In this paper we analyze the damage a Category 3 hurricane inlicted on a 200-700 AD pyramid located on the coastal plain 6 km inland from the Gulf of Mexico in a humid tropical environment. The evaluation is part of an ongoing preservation program. On the one hand, we report the good performance of a protection strategy consisting of a geotextile covered with an earthen sacriicial layer with very low proportions of vinyl polymers and a silane-siloxane water repellent. On the other hand, we analyze the deterioration and collapse of a section of building ill, caused by the hurricane itself, but also by the heavy rains and afterwards the severe drying period that followed the event. We also evaluate factors of mineral composition of building sediments, rain impact, wind direction, and intrusive vegetation. Based on the evaluation we consider alternatives for the preservation of archaeological earthen architecture in cases of hurricane impact.